ANALYSIS AND CONCLUSION OF THE CASE MIXED DNA SAMPLES IN FORENSIC EXAMINATION BY RELATIVE FLUORESCENSE UNIT METHOD - Nguyen Thi Hoa; Nguyen Thi Le Dan; Nguyen Tien Tung (Tạp chí Y học Quân sự, 2023)
Purpose: We aimed to extract mixed DNA samples collected from the crime scene into DNA profiles and provided an accurate assessment of which contributor DNA belongs to the culprit. Methods: We analyze the nuclear DNA (nDNA) from DNA mixtures and amplify genes with the GlobalFiler 24 Locus Gene (Thermo Fisher, USA) kit, followed by capillary electrophoresis using the Genetic Analyzer 3500 System. Data analysis was performed using Genemapper ID_X software and interpreting the results by calculating the Relative Fluorescence Unit (RFU). Conclusion: The method of analyzing the results using RFU for short repeat sequences (STRs) of the nuclear genome is highly reliable and current, applied in most of the advanced countries in the world. Therefore, the International Society of Forensic Genetics has encouraged and prioritized this method.